Decidualized Endometrioma Masquerading as Ovarian Cancer in Pregnancy. (1st November 2014) - Groszmann, Yvette; Howitt, Brooke E.; Bromley, Bryann; Feltmate, Colleen M.; Benacerraf, Beryl R.
Abstract : Objectives: To identify the sonographic features of decidualized endometriomas in patients treated at a single institution and to determine whether sonographic findings can distinguish these lesions from malignant ovarian tumors during pregnancy. Methods: We conducted a retrospective cohort study that included pregnant women with a histologic diagnosis of decidualized endometrioma between January 1, 2005, and December 1, 2012, and had an ovarian cyst or mass seen preoperatively on obstetrical sonography. Sonographic characteristics of these masses were retrospectively evaluated using the International Ovarian Tumor Analysis Group definitions for adnexal masses. Results: Seventeen patients with 22 adnexal masses were included in our study. Nine of 22 lesions (41%) were classified as unilocular solid, and 14 of 22 (64%) had solid components, of which 12 of 14 (86%) had substantial blood flow. Septations were present in 8 of 22 masses (36%). Cyst sizes varied from 30 to 120 and 32 to 270 mm at the initial and follow‐up scans, respectively. Eight patients had no follow‐up scans and underwent surgery within 3 weeks of diagnosis. The other 9 patients (14 masses), had follow‐up scans and underwent surgery from 3 to 34 weeks after their initial scans. Eight of these masses showed no notable change in size or appearance, and 1 became smaller. Conclusions: There were no characteristic sonographic features identified to distinguish decidualized endometrioma from ovarian malignancy. However, lesions showing no change in size over 4 weeks or lacking solid components and vascularity are more likely to be benign rather than malignant and may justify delaying surgery until delivery or postpartum.